Investigation of Effect of Labour and Road Infrastructure on Fermented Dairy Production Capacity in Upstream Fermented Dairy Supply Chain - Ceyhun Serçemeli; Ensar Balkaya; Abdullah Tüzemen (Journal of Agricultural Sciences)
Scope of the study focuses on fermented dairy products because, they constitute very large and important part of human diet. These products are very healthy because, they have some health benefits. 2731 fermented dairy processors in 227 sub-sectors in 48 cities have been investigated to determine the effect of the length of roads, the number of white-collar and blue-collar employees on fermented dairy production capacity. To do that, Generalized Linear Model has been utilized. Consequently, results state that the number of blue-collar employees has a positive effect on fermented dairy production capacity at 0.001 significance while the number of white-collar employees does not have a significant effect on the fermented dairy production capacity. On the other hand length of road has a positive effect on the fermented dairy production capacity at 0.10 significance level.